PENDIDIKAN AGAMA ISLAM IDEAL BAGI DIFABILITAS - Mahmudin, Afif Syaiful (AS-SALAM, 2017)
Education fairness being the important thing to note in this nation. The House should not be disabled again getting marginalized place. They have the same right to a decent education ". So the potential they possess could develop with optimal. Every human being is created with all that perfection, then human perfection is not diminished by the lack of a physical condition. This research aims to examine the importance of organized school inclusion, especially the material of Ideal Religious Education for persons with disabilities. Library research methods used over the excavation information from a variety of literature-related education for the disabled. The results show that all schools can be the school inclusion. Of course with increased competence of teachers in designing learning so that it can be accepted by people with diffabilities. Keywords: islamic education, equitable education, diffability, school inclusion